The impact of coronary artery bypass grafting added to aortic valve replacement on long-term outcomes in octogenarian patients: a reconstructed time-to-event meta-analysis. (20th June 2022) - Gallingani, Alan; D'Alessandro, Stefano; Singh, Gurmeet; Hernandez-Vaquero, Daniel; Çelik, Mevlüt; Ceccato, Evelina; Nicolini, Francesco; Formica, Francesco
Summary: The long-term results in studies comparing octogenarian patients who received either isolated surgical aortic valve replacement (i-SAVR) or coronary artery bypass grafting (CABG) in addition to SAVR are still debated. We performed a reconstructed time-to-event data meta-analysis of studies comparing i-SAVR and CABG+SAVR to evaluate the impact of CABG and to analyse the time-varying effects on long-term outcome. We performed a systematic review of the literature from January 2000 through November 2021, including studies comparing i-SAVR and CABG+SAVR, which reported at least 3-year follow-up and that plotted Kaplan–Meier curves of overall survival. The primary endpoint was overall long-term survival; secondary endpoints were in-hospital/30-day mortality and postoperative outcomes. The pooled hazard ratio (HR) and odds ratio) with 95% confidence interval (CI) were calculated for primary and secondary endpoints, respectively. Random-effect model was used in all analyses. Sixteen retrospective studies were included (5382 patients, i-SAVR = 2568 and CABG+SAVR = 2814). I-SAVR showed a lower incidence of in-hospital mortality compared to CABG+SAVR (odds ratio = 0.73; 95% CI= 0.60–0.89; P = 0.002). Landmark analyses showed a significantly higher all-cause mortality within 1 year from surgery in CABG+SAVR (HR = 1.17; 95% CI = 1.01–1.36; P = 0.03); after 1 year, no significant difference was observed (HR = 0.95; 95% CI = 0.87–1.04; P = 0.35). Landmark analysis was confirmed by time-varying trend of HR. Late survival of octogenarians did not differ significantly between the 2 interventions. Interestingly, CABG added to SAVR was associated with both higher in-hospital and within 1-year mortality after surgery, whereas this difference was statistically non-significant at long-term follow-up. Abstract : Aortic valve stenosis (AS) and coronary artery disease (CAD) are the most common cardiac diseases in the aged population, and as the octogenarian population will rise in the coming decades, there will also be a concomitant increase in patients with AS and CAD.